2005
DOI: 10.17660/actahortic.2005.673.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Certain Pre-Treatment Substances on Vase Life and Physiological Character in Lilium Spp.

Abstract: The effects of pre-treatment substances on vase life and physiological character of cut Lilium Oriental hybrid 'Siberia' and Lilium Asiatic hybrid 'Dream Land' were studied. When florets of 'Siberia' were treated with Promalin (GA 4+7 +BA), the vase life was increased as compared to other treatments. The amount of ethylene produced continuously decreased and respiration rate showed a climacteric type rise on the 5 th day. The sugar contents increased in petal, but decreased in leaf and ovary. When florets of '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 8 publications
3
23
1
2
Order By: Relevance
“…it influenced the growth of meristematic sprouts in tissue culture (Nge et al, 2006), and in Lilium spp. It displayed an increase in vase life when the stems were submerged in, or sprayed with, a solution of chitosan + pure AG colloidal nanoparticle + ion (Kim et al, 2005). There is other evidence, such as that described by Ohta et al (2001), who reported that seeds from lisianthus (Eustoma grandiflorum (Raf.)…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…it influenced the growth of meristematic sprouts in tissue culture (Nge et al, 2006), and in Lilium spp. It displayed an increase in vase life when the stems were submerged in, or sprayed with, a solution of chitosan + pure AG colloidal nanoparticle + ion (Kim et al, 2005). There is other evidence, such as that described by Ohta et al (2001), who reported that seeds from lisianthus (Eustoma grandiflorum (Raf.)…”
Section: Discussionmentioning
confidence: 91%
“…influyó en el crecimiento de brotes meristemáticos en cultivo de tejidos (Nge et al, 2006) y en Lilium spp. mostró un incremento en la vida de florero cuando los tallos fueron sumergidos o asperjado con una solución de quitosano + nano partícula coloidal pura AG + ion (Kim et al, 2005). Otras evidencias, tales como la descrita por Ohta et al (2001), quienes reportaron que semillas de lisianthus (Eustoma grandiflorum (Raf.)…”
Section: Discussionunclassified
“…Effects of NS as a dip or spray pre-treatment on the subsequent vase life and physiology of cut Lilium Oriental hybrid 'Siberia' and Lilium Asiatic hybrid 'Dream Land' were investigated by Kim et al (2005). The vase life of Lilium 'Siberia' florets was extended with a treatment comprised of 0.1% NS plus natural chitosan.…”
Section: Metal Ions 221 Silvermentioning
confidence: 99%
“…NS releases silver ions (Ag + ) within bacterial cells, which enhance its bactericidal activity (Feng et al, 2000;Rai et al, 2009). In cut flower applications, NS has been reported to be effective as an antimicrobial agent (Liu et al, 2009a;Solgi et al, 2009;Lv et al, 2010a), an ethylene inhibitor (Kim et al, 2005) and/or a regulator of stomatal aperture (Lv et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%